2009
DOI: 10.1002/j.0022-0337.2009.73.5.tb04737.x
|View full text |Cite
|
Sign up to set email alerts
|

Work‐Related Musculoskeletal Disorders Among Brazilian Dental Students

Abstract: The aim of this analytical cross‐sectional study was to evaluate the presence of work‐related musculoskeletal disorders (WMSD) among dental students in two Brazilian dental schools. The sample included 227 randomized subjects from fifth to ninth semesters who were developing clinical activities. Each student signed an informed consent form. A self‐reporting questionnaire was used to obtain data on the practice of physical exercise, the presence of pain during or soon after treating patients, and the adoption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 8 publications
3
53
1
2
Order By: Relevance
“…The prevalence of musculoskeletal pain among dental students in this study was lower than in other studies (2,(21)(22)(23)(24)(25)(26)(27). In accordance to other studies the prevalence of musculoskeletal pain was higher in women than men (2,6,21,23,25,28,31), nevertheless, the difference was on the limit of statistical significance. A difference was found between the years of studies, however it was not statistically significant.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The prevalence of musculoskeletal pain among dental students in this study was lower than in other studies (2,(21)(22)(23)(24)(25)(26)(27). In accordance to other studies the prevalence of musculoskeletal pain was higher in women than men (2,6,21,23,25,28,31), nevertheless, the difference was on the limit of statistical significance. A difference was found between the years of studies, however it was not statistically significant.…”
Section: Discussionsupporting
confidence: 82%
“…Hodačová et al (6) found an influence of the severe disease or injury of the locomotive apparatus on the musculoskeletal pain among dental practitioners. In the study of De Carvalho et al (21) regularly doing exercises didn't have any influence on musculoskeletal pain, whereas Shirzaei et al (28) proved a lower average intensity of pain in students, who did stretching after the patients treatment. In the study of Sharma et al (20) 80% of responding dentists declared, that the cause of their pain was the lack of physical activity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, it becomes clear that dentists and dental hygienists and therapists are at particularly high risk of developing MSDs during their careers. These may occur as early as undergraduate training with debilitating consequences on the clinician's practising live and well‐being. MSDs are a common reason for dentists and dental hygienists to seek medical care and being absent from work .…”
Section: Introductionmentioning
confidence: 99%
“…Significant MSDs risk factors specific to dental prac- Some researchers suggest that MSDs in dental practitioners begin as early as clinical training period at dental school [26][27][28]. In two separate studies in Iran and Spain, near 80% of dental students reported body pain in at least one body region [29,30].…”
Section: Introductionmentioning
confidence: 99%